2016
DOI: 10.3109/13880209.2015.1120322
|View full text |Cite
|
Sign up to set email alerts
|

Hypouricaemic action of mangiferin results from metabolite norathyriol via inhibiting xanthine oxidase activity

Abstract: Context Mangiferin has been reported to possess a potential hypouricaemic effect. However, the pharmacokinetic studies in rats showed that its oral bioavailability was only 1.2%, suggesting that mangiferin metabolites might exert the action. Objective The hypouricaemic effect and the xanthine oxidase inhibition of mangiferin and norathyriol, a mangiferin metabolite, were investigated. Inhibition of norathyriol analogues (compounds 3-9) toward xanthine oxidase was also evaluated. Materials and methods For a dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…The three polyphenols tested here have free radical quenching capacity (González-Gallego et al, 2010 ; Braakhuis and Hopkins, 2015 ; Luo et al, 2017 ; Rauf et al, 2017 ), being also inhibitors of XO (Pinto et al, 2005 ; Paredes-Gonzalez et al, 2015 ; Niu et al, 2016 ) and NOX (Makino et al, 2013 ; Xia N. et al, 2014 ). However, no study in humans has shown that antioxidants, even when administered intravenously are capable of enhancing peak power output during repeated prolonged sprint exercise.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The three polyphenols tested here have free radical quenching capacity (González-Gallego et al, 2010 ; Braakhuis and Hopkins, 2015 ; Luo et al, 2017 ; Rauf et al, 2017 ), being also inhibitors of XO (Pinto et al, 2005 ; Paredes-Gonzalez et al, 2015 ; Niu et al, 2016 ) and NOX (Makino et al, 2013 ; Xia N. et al, 2014 ). However, no study in humans has shown that antioxidants, even when administered intravenously are capable of enhancing peak power output during repeated prolonged sprint exercise.…”
Section: Discussionmentioning
confidence: 96%
“…Luteolin (30, 40, 50, 70-tetrahydroxyflavone) is one of the most abundant flavones and, like mangiferin and quercetin, is a potent antioxidant and inhibitor of xanthine oxidase (XO) (Nagao et al, 1999 ; Pinto et al, 2005 ; Paredes-Gonzalez et al, 2015 ; Niu et al, 2016 ; Nile et al, 2017 ). Luteolin is also a NADPH oxidase (nicotinamide adenine dinucleotide phosphate-oxidase; NOX) inhibitor (Makino et al, 2013 ; Xia F. et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Natural polyphenols like mangiferin and luteolin are potent antioxidants and inhibitors of XO [23,38,39] and NOX [40,41]. A previous study has shown ergogenic effects after acute supplementation (48 h) with a mango leave extract (MLE, Zynamite ® ) combined with either quercetin or luteolin [27].…”
Section: Introductionmentioning
confidence: 99%
“…Mangiferin (2-bD-glucopyranosyl-1,3,6,7-tetrahydroxyxanthone) is a xanthone abundant in the leaf and pulp of mangoes, which is also present in other edible vegetables [20]. Mangiferin has iron-chelating properties, free-radical scavenging capacity and inhibits some of the oxidases involved in oxidative stress and inflammation [7,9,[21][22][23][24]. For these reasons, a natural extract rich in mangiferin may mitigate or prevent EIMD.…”
mentioning
confidence: 99%